2015
DOI: 10.4244/eijy14m10_06
|View full text |Cite
|
Sign up to set email alerts
|

Bioresorbable vascular scaffold treatment induces the formation of neointimal cap that seals the underlying plaque without compromising the luminal dimensions: a concept based on serial optical coherence tomography data

Abstract: Neointimal tissue develops following either Absorb BVS or BMS implantation and shields lipid tissues. The neointimal response in the BMS causes a higher reduction of luminal dimensions compared to the Absorb BVS. Thus, Absorb BVS may have a value in the invasive re-capping of high-risk plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Thus, DCB angioplasty as a stand-alone procedure might be a promising trade-off between POBA, DES, and BVS. On the other hand, it has been shown that BVS has the capacity to “seal” underlying coronary plaques [39, 42]. Whether or not this translates into a favorable long-term course remains nevertheless unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, DCB angioplasty as a stand-alone procedure might be a promising trade-off between POBA, DES, and BVS. On the other hand, it has been shown that BVS has the capacity to “seal” underlying coronary plaques [39, 42]. Whether or not this translates into a favorable long-term course remains nevertheless unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Bioresorbable vascular scaffolds (BVS) have recently been introduced as a novel approach for treatment of coronary artery disease, providing transient vascular support and drug delivery, potentially restoring the vascular physiology after device bioresorption [1][2][3][4] . The theoretical advantages of this novel technology, such as late lumen enlargement, restoration of coronary vasomotion and plaque sealing, make this device appealing for patients with ruptured thincapped lipid-rich soft plaques in general [5][6][7] and thrombotic lesions in acute coronary syndromes and STEMI in particular [8][9][10] . Due to vasoconstriction and presence of thrombus, the treatment of acute lesions is often associated with device undersizing and the occurrence of malapposition after thrombus resolution.…”
Section: Abstract • Bioresorbable Vascular Scaffolds (Bvs) • Percutanmentioning
confidence: 99%
“…The neointimal response in the BMS causes a higher reduction of luminal dimensions compared with the Absorb stent with documented late lumen enlargement. Thus, the Absorb stent may have a value in the invasive re-capping of high-risk plaques [89,90]. One OCT study demonstrated that after an Absorb stent implantation neointimal tissue develops that covers almost the whole circumference of the vessel wall.…”
Section: Hot Topics In 2015mentioning
confidence: 99%